PENGGUNAAN MODEL PEMBELAJARAN VISUALIZATION AUDITORY KINESTETIC (VAK) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DI KELAS V-A UPT. SD NEGERI 01 LIMO KAUM - Ferawati, Ferawati (Ensiklopedia Education Review, 2021)
A structural learning model that can use several methods, techniques and learning strategies at once, the learning model must be student-centered so that learning objectives can be achieved. However, the reality is that learning in the classroom tends to be centered on the teacher (teacher centered learning) so that students are more dominant passive than active, this has an impact on student learning outcomes to be low. The research questions in this study are how the teacher's activities, student activities, and how to improve student learning outcomes in class V-A UPT. SD Negeri 01 Limo Kaum. This research is a field research using quantitative and qualitative methods. Data were collected through observation and tests, then the data were analyzed using a percentage formula. The results of the study found that the activity of the teacher in cycle I reached 71.88%, in cycle II reached 76.56% and cycle III reached 95.31%. Student activity in cycle I reached 70.31%, cycle II reached 75%, and in cycle III 87.5%. The learning outcomes of students who completed the first cycle reached 68.57%, the second cycle reached 82.86%, and the third cycle reached 91.43%. Thematic learning is getting better with the Visualization Auditory Kinesthetic (VAK) model to improve student learning outcomes because this learning model combines the three learning modalities to make students feel comfortable and the learning perceived by students feels more meaningful.